The old devils - Amis, Kingsley, author (England : Penguin Books, 1987)
Malcolm, Peter and Charlie and their Soave-sodden wives have one main ambition left in life: to drink Wales dry. But their routine is both shaken and stirred when they are joined by professional Welshman Alun Weaver (CBE) and his wife, Rhiannon, returning to their Celtic roots